CREATION OF A WORDWALL-BASED COGNITIVE ASSESSMENT TOOL FOR STATIC ELECTRICITY MATERIALS - Angelika, Neindea; Lestari, Wahyu (Jurnal Pendidikan Matematika dan IPA, 2024)
Cognitive assessment of kids who still frequently use paper documents and certain school-provided software. The objective of this study is to develop a legitimate, dependable, efficient, and useful tool that may be used to teach static electricity concepts through wordwalls. This study use the ADDIE model in conjunction with the Research and Development technique. Purposive sampling is the sampling strategy used, taking into account samples that have finished the science learning material on static electricity. There were 57 individuals in the sample. The SMP 42 Negeri in Semarang City is the research location. Using SPSS software version 2019 and Ministep, the data analysis technique involves testing the validity, reliability, efficacy, and practicality of test instruments and questionnaires.The study's findings demonstrate that the creation of a wordwall-based cognitive instrument on static electricity learning outcomes is valid, dependable (having received an adequate category score of 0.74), successfully executed (having received an average score of 74.8), and practically implemented (producing 66.4% of the responses from students). This means that future researchers can build on this tool to suit their needs and the reference tools that are used to assess learning.